Disinfection of Horticultural Tools - Geoffrey C. Denny; Gary E. Vallad (EDIS)
ENH-1121, a 2-page fact sheet by Geoffrey C. Dennny and Gary E. Vallad, provides assistance to producers and home gardeners in selecting the appropriate method to sterilize or disinfect horticultural tools and implements to prevent the spread of disease-causing pathogens. Published by the UF Department of Environmental Horticulture, August 2009.